Criminal Procedure Undergraduate Edition Author - Smith, Christopher E.; Trachtenberg, Ben; Alexander, Anne (Open textbook library., 2022)
An open textbook for undergraduate Criminal Procedure courses that are typically required of criminal justice majors. The book uses U.S. Supreme Court opinions to illuminate the definition of rights concerning search and seizure, right to counsel, and other aspects of the criminal justice process. This open textbook seeks to make undergraduates familiar with judicial reasoning as well as the definitions of rights relevant to individuals who are drawn into contact with criminal justice officials. The chapters give significant attention to police procedures and individual rights under the Fourth Amendment related to searches, including those using warrants and the situations in which warrant searches are permissible. The book also covers rights in the context of police interrogation, including Miranda warnings and exceptions to the Miranda rule. In addition, there is coverage of the exclusionary rule, right to counsel, plea bargaining, and trial rights. It concludes with a brief examination of rights related to sentencing. This resource challenges undergraduates to understand the development and changes affecting rights as new decisions are issued by the U.S. Supreme Court.